A psychometric lens for e-learning: Examining the validity and reliability of the persian version of University Students’ Engagement Inventory (P-USEI) - Sharif Nia, Hamid (2022)
Student engagement is a critical component of e-learning, which became an important focus for most academic institutions during the COVID-19 pandemic. University students’ engagement is measured using various scales with diferent subscales. This study aimed to evaluate the psychometric properties of the Persian version of the University Student Engagement Inventory (P-USEI). A cross-sectional methodology study was conducted among Iranian university students (n =667) from April to May 2020. After forward–backward translation, the content, and construct validity, and reliability of the scale were assessed. The results obtained from the confrmatory factor analysis confrmed that the P-USEI has three factors: cognitive, emotional, and behaviour. The fndings of the study supported the adequate reliability, factorial, convergent, and discriminant validities of P-USEI in a sample of Iranian students. The P-USEI dimensions have predictive value for important academic variables that can be generalized by developing the research through a psychometric evaluation on student engagement.